Structure elucidation of constituents of the preorbital secretion of the grysbok Raphicerus melanotis - Tien, Feng-Chang (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1993.